Chief Justice Fred M. Vinson of Kentucky : a Political Biography. - St. Clair, James E. (The University Press of Kentucky, 2015)
Fred M. Vinson, the thirteenth Chief Justice of the United States, started his political career as a small-town Kentucky lawyer and rose to positions of power in all three branches of federal government. Born in Louisa, Kentucky, Vinson earned undergraduate and law degrees from Centre College in Danville. He served 12 years in the U.S. House of Representatives, where he achieved acclaim as a tax and fiscal expert. President Roosevelt appointed him to the U.S. Circuit Court of Appeals for the District of Columbia and later named him to key executive-branch positions. President Truman appointed.